Tricellulin Is a Tight-Junction Protein Necessary for Hearing - Riazuddin, Saima (American Society of Human Genetics, 2006)
The inner ear has fluid-filled compartments of different ionic compositions, including the endolymphatic and perilymphatic spaces of the organ of Corti; the separation from one another by epithelial barriers is required for normal hearing. TRIC encodes tricellulin, a recently discovered tight-junction (TJ) protein that contributes to the structure and function of tricellular contacts of neighboring cells in many epithelial tissues. We show that, in humans, four different recessive mutations of TRIC cause nonsyndromic deafness (DFNB49), a surprisingly limited phenotype, given the widespread tissue distribution of tricellulin in epithelial cells. In the inner ear, tricellulin is concentrated at the tricellular TJs in cochlear and vestibular epithelia, including the structurally complex and extensive junctions between supporting and hair cells. We also demonstrate that there are multiple alternatively spliced isoforms of TRIC in various tissues and that mutations of TRIC associated with hearing loss remove all or most of a conserved region in the cytosolic domain that binds to the cytosolic scaffolding protein ZO-1. A wild-type isoform of tricellulin, which lacks this conserved region, is unaffected by the mutant alleles and is hypothesized to be sufficient for structural and functional integrity of epithelial barriers outside the inner ear.